"Italian Regionalism and the Federal Challenge" - Arban, Erika (Université d'Ottawa / University of Ottawa, 2015)
This thesis takes as its point of departure the debate on federalism that emerged in Italy in the years preceding the unification of 1861 and that resumed in the early 1990s, a debate mainly revolving around the profound socio-economic differences between the North and the South of the country. Torn between continuous centripetal and centrifugal forces, but not characterized by ethnic connotations, the Italian regional model implemented with the 1948 constitution and strengthened in 2001 elicits questions that intersect with topical debates engaging scholars across the globe, and displays features that have the potential to stimulate fruitful discussions both inside and outside Italian borders. While the present state of Italian regionalism remains ambiguous, the Italian regional model distils lessons coming from different theoretical experiences, including federalism, sub-state nationalism, and the European unification process. Therefore, it can be seen as an innovative experiment crafted by those who were looking for a compromise between unitary and federal schemes. Adopting a theoretical framework combining literature on federalism, regionalism and sub-state national theory, this thesis addresses a number of questions that help fill a gap in scholarship. The thesis discusses the relationship between federalism and regionalism, arguing that regionalism is an overarching term that incorporates diverse experiences; consequently, the regional state paradigm to which Italy is usually associated is just one of the many shapes that regionalism can take. The research also identifies the elements enabling us to differentiate between a federal and a regional model, as well as the advantages of opting for a regional scheme (as opposed to a federal one). The socio-economic tensions between the North and the South of Italy offer the ideal basis to discuss non-national differences, an expression used to indicate political and socio-economic communities located within a geographical territory displaying some de facto asymmetries compared to the state-wide community, seeking some form of acknowledgement of their specificity. The thesis argues that national differences (e.g. differences based on linguistic, religious or other cultural issues) are not the only ones requiring attention, and it identifies a number of legal and constitutional stratagems that could be used to address non-national difference. Also, the recognition of non-national difference may also help find a solution to issues regarding sub-state national recognition. Finally, the thesis tries to find a point of reconciliation between federalism and solidarity, particularly in the context of non-national difference. The Italian regional experience serves once again as the point of departure to discuss whether federalism and solidarity are conflicting ideas, and to open a discussion regarding the exact contours of solidarity, especially in its horizontal understanding.
Keywords: Italy; Regionalism; Federalism; Solidarity; Subsidiarity